Engaging Stakeholders to Optimize Sleep Disorders' Management in the U.S. Military: A Qualitative Analysis. Issue 7 (23rd August 2021) - Abdelwadoud, Moaz; Collen, Jacob; Edwards, Hillary; Mullins, C Daniel; Jobe, Sophia L; Labra, Christian; Capaldi, Vincent F; Assefa, Samson Z; Williams, Scott G; Drake, Christopher L; Albrecht, Jennifer S; Manber, Rachel; et al.
ABSTRACT: Introduction: Sleep disorders' are highly prevalent among U.S. active duty service members (ADSMs) and present well-documented challenges to military health, safety, and performance. In addition to increased need for sleep medicine services, a major barrier to effective sleep management has been a lack of alignment among patients, health providers, and economic-decision-makers. To address this gap in knowledge, the purpose of the present study was to engage diverse stakeholders vested in improving sleep disorders' management in the military. Materials and Methods: We elicited feedback from ADSMs with sleep disorders (five focus group discussion, n  = 26) and primary care managers (PCMs) (11 individual semi-structured interview) in two military treatment facilities (MTFs) in the National Capitol Region, in addition to national level military and civilian administrative stakeholders (11 individual semi-structured interview) about their experiences with sleep disorders' management in U.S. MTFs, including facilitators and barriers for reaching a definitive sleep diagnosis, convenience and effectiveness of sleep treatments, and key desired outcomes from interventions designed to address effectively sleep disorders in the U.S. military health care system (MHS). Recordings from focus groups and semi-structured interviews were transcribed verbatim and analyzed using QSR International's NVivo 12 software using inductive thematic analysis. The study was approved by Walter Reed National Military Medical Center Department of Research Programs. Results: Active duty service members with sleep disorders often fail to recognize their need for professional sleep management. Whereas PCMs identified themselves as first-line providers for sleep disorders in the military, patients lacked confidence that PCMs can make accurate diagnoses and deliver effective sleep treatments. Active duty service members cited needs for expeditious treatment, educational support and care coordination, and support for obtaining sleep treatments during deployment. Challenges that PCMs identified for effective management include insufficient time during routine care visits, delays in scheduling testing procedures, and limited number of sleep specialists. Primary care managers suggested offering evidence-based telehealth tools and enhanced care coordination between PCMs and specialists; standardized medical education, materials, and tools; patient preparation before appointments; self-administered patient education; and including behavioral sleep specialists as part of the sleep management team. For administrative stakeholders, key outcomes of enhanced sleep management included (1) improved resource allocation and cost savings, and (2) improved ADSM safety, productivity, and combat effectiveness. Conclusion: Current military sleep management practices are neither satisfactory nor maximally effective. Our findings suggest that solving the military sleep problem will require sustained effort and ongoing collaboration from ADSM patients, providers, and health systems leaders. Important potential roles for telehealth and technology were identified. Future research should seek to enhance implementation of sleep management best practices to improve outcomes for patients, providers, MHS, and the military as a whole.